Development of multi-level standards of care recommendations for sickle cell disease: Experience from SickleInAfrica - Paintsil, Vivian; Ally, Mwashungi; Isa, Hezekiah; Anie, Kofi A.; Mgaya, Josephine; Nkanyemka, Malula; Nembaware, Victoria; Oppong-Mensah, Yaa Gyamfua; Ndobho, Flora; Chirande, Lulu; Makubi, Abel; Nnodu, Obiageli; et al. (Frontiers in Genetics, 2023)
Introduction Sickle Cell Disease (SCD) causes significant morbidity and mortality particularly in sub-Saharan Africa (SSA) where it contributes to the high public health burden, and to early childhood deaths if no interventions are put in place. There is need to implement strategies and treatment guidelines to help improve overall SCD patient health outcomes through standardization of quality care. We set out to review existing guidelines on SCD and to set minimum standards for management of SCD for the different referral levels based on institutional and human resources. Methods A standards of care working group (SoC-WG) was established to develop the SoC recommendations for use in the various referral levels of healthcare. About 15 available SCD management guidelines and protocols from US, UK, France, Brazil and Jamaica and from the 3 sites in Sickle Pan African Research Consortium (SPARCo) and Sickle Africa Data Coordinating Centre (SADaCC) were reviewed and themes extracted from them. The first draft was on chosen themes with major headings as follows: Diagnosis of SCD and related conditions, health maintenance and preventive therapy, screening for specific complications of SCD, management of acute complications of SCD, management of chronic complications of SCD and special management protocols. Using a summarised WHO levels of referral document, lower level recommendations for SCD management were compiled. Results The results from this review yielded a guidelines document which had recommendations for management of SCD based on the institutional and human capacity for all the different referral levels. Discussions It is essential that every child with SCD receives comprehensive care that is coordinated at each level by medical experts using guidelines. This recommendation is unique in terms of the availability of recommendations for different levels of care as compared to the traditional guidelines which is more focussed at the tertiary levels. Conclusion This SoC recommendations document is a useful material that can be used for consistent standards of treatment in SSA.